The Effectiveness of Special Exercises in Improving The Optimal Speed of The Approach Phase and Their Effect on The Distance of The Long Jump - Jasim, Taha Abdulelah Jasim (Pubmedia Jurnal Pendidikan Olahraga, 2026)
The research aims to identify the effectiveness of special exercises in improving the optimal speed of the approach phase and their effect on the distance of the long jump among long jump athletes. The researcher used the experimental method with a pre-test and post-test design for one experimental group, due to its suitability for the nature of the research. The research sample was intentionally selected from long jump athletes, and their number reached (8) athletes, The researcher used a set of tests to measure the optimal speed of the approach phase, represented in the full approach run test (30 m), the 20 m flying speed test, step frequency in the last 10 m, the length of the last three steps, and the accuracy of rhythmic adjustment of the approach mark, in addition to measuring the digital level of the long jump ,The researcher applied a proposed training program using special exercises that lasted for 8 weeks at a rate of 3 training units per week. The results of the research showed the presence of statistically significant differences between the pre-test and post-test measurements of the experimental group in the tests of optimal speed of the approach phase and the digital level of the long jump in favor of the post-test measurement, The results also showed the presence of a positive statistically significant correlation between the improvement of the optimal speed of the approach phase and the improvement of the long jump distance. In light of these results, the researcher recommends the necessity of paying attention to the use of special exercises in training long jump athletes due to their positive effect in improving approach speed, developing technical performance, and increasing the digital level in the long jump.